Bharatiya Mazdoor Sangh: An introductory study - Ragi, Sangit Kumar (2015)
This article attempts to make an introductory study of (BMS)- a major organisation of Sangh Pariwar. BMS primarily deals with the problems of the Indian working class, though it seeks to work in overall perspective of national intrest. Its entire ideological orientation has been summed up in three major slogans; 'Nationalise the Labour, Labourise the Industry, and Industrialise the Nation'. Thus it is clear that BMS, despite being a labour organisation, does not believe in class conflict and class struggle. It goes without saying that it has a different vision of trade unionism as compared to other major working class organisations like All India Trade Union Congress (AITUC), Indian National Trade Union Congress (INTUC), Hind Mazdoor Sabha (HMS) and others. It is inspired by Indian nationalism and Integral Humanism as enunciated by Deendayal Upadhayay. It was founded by Dattopant Thengadi in 1955. It has been working in different sectors with special emphasis on unorganised labour designated as Vishwakarma. At times it has the courage of conviction to swim against the dominant currents of trade unionism.
Keywords: Bharatiya Mazdoor Sangh; Trade unions